PENGEMBANGAN MODUL MATEMATIKA UNTUK SISWA KELAS 3 SEKOLAH DASAR NEGERI WUJIL 01 BERGAS - Mochamad Rizqi Adhi Pratama; Nur Intan Rochmawati (Universitas Negeri Medan, 2019)
Abstract: Development of Mathematics Modul For Students Elementary School Class 3 in Wujil 01 Bergas. This study purpose to produce a more interactive mathematical module that is feasible to be used as a support for teaching materials for grade 3 students of Wujil 01 Bergas State Elementary School. This research method uses Research and Development (R&D) and the development of Borg and Gall, 1989 (in Sukmadinata, 2011), implementation with a study population of 34 students. Research site at SD Negeri Wujil 01 Bergas. The product produced from this development is mathematics teaching material to support teaching materials for grade 3 students of SD Negeri Wujil 01 Bergas. The results of this study are mathematical modules suitable for use in grade 3 students at SD Negeri Wujil 01 Bergas.Keywords: Modules, Mathematics, Elementary Students.Abstrak: Pengembangan Modul Matematika Untuk Siswa Kelas 3 Sekolah Dasar Negeri Wujil 01 Bergas. Penelitian ini bertujuan untuk menghasilkan modul matematika yang lebih interaktif yang layak untuk digunakan sebagai penunjang bahan ajar siswa kelas 3 Sekolah Dasar Negeri Wujil 01 Bergas. Metode penelitian ini menggunakan Research and Development (R&D) dan pengembangan dari Borg dan Gall, 1989 (dalam Sukmadinata, 2011), implementasi dengan populasi penelitian sebanyak 34 orang siswa. Tempat penelitian di SD Negeri Wujil 01 Bergas. Produk yang dihasilkan dari pengembangan ini adalah bahan ajar matematika sebagai penunjang bahan ajar siswa kelas 3 SD Negeri Wujil 01 Bergas.Kata Kunci: Modul, Matematika, Siswa SD.